Stress Analysis in the Extrusion of Bimetallic Tubes - Alcaraz, J.L.; Martínez-Esnaola, J.M.; Gil-Sevillano, J. (Engineering Transactions, 1997)
Stress analysis of the flow of a bimetallic tube in the process of extrusion through a conical die is presented in this paper. Two materials are involved in the process, one of them being of lower thickness and exhibiting finer properties than the other. The stress field is determined by assuming an axially-symmetric radial flow and material incompressibility, with no velocity discontinuity along the material interface and including friction between the bimetallic tube and the tools. Different extrusion conditions and different material combinations are compared to assess their influence on the stress levels in critical zones for the two possible locations of the finer material. It is concluded that the most influential parameters seem to be the yield stress ratio and the friction with the die.